Economic Feasibility of Integrated Agriculture Pattern for Bali Cattle (Bos Javanicus) in North Central Timor Regency - Alfridis Thaal; Werenfridus Taena; Umbu Joka (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
This study aims to: (1). know the economic feasibility of integrated livestock farming in North Central Timor Regency. (2). Describe the feasibility of integrated livestock farming from an economic aspect in North Central Timor Regency. The analysis used in this research are descriptive and economic feasibility analysis (R/C ratio). The data obtained are in the form of primary data and secondary data. The results of the descriptive analysis show that the potential that is owned, such as the availability of paddy field with an average of 37.85 acres / person and upland land with an average of 45.54acres / person are able to produce an average of 407.26 kg / year / person of rice, 501.33 kg / year / person of corn. So that it can produce agricultural crop waste such as rice straw amounting to 6.109 tons / ha / year and corn waste of 7.520 tons / ha / year. It can be said that rice and corn agricultural waste is able to help the availability of feed for cattle as much as 4 cows / year. The feasibility of the integration pattern of farming and livestock in TTU regency is feasible. The results of the R / C Ratio analysis, is 8.44 (R / C Ratio> 1) with a revenue of Rp.607,405,000 of the total cost incurred of Rp.192,000,000.